Macroeconomic Impacts of Demographic Change - Michalski, Michal A. (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter explores the relationship between demographic change and the macroeconomic condition of society. It describes three approaches to population growth that are present within economic theory and demonstrates how the last decades have offered evidence that demographic growth should generally not be seen as a threat to socio-economic development. In addition, the chapter discusses selected aspects of the economy in the context of the influence of demographic decline. In connection to this, it presents the simplified scheme of the process of the influence of a decrease in fertility and population ageing on economic stagnation. Finally, the impact of the quality, structure, and stability of the family environment on the economy is examined in the context of positive outcomes such as human and social capital.Keywords: demographic change, economy, macroeconomic impact, development, family.